2023
DOI: 10.1021/acs.langmuir.2c03386
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organization of Mobile, Polyelectrolytic Dendrons on Stable, Amphiphile-Based Spherical Surfaces

Abstract: Spherical surfaces bearing mobile, solvophilic chains are ubiquitous. These systems are found in nature in the form of biological cells bearing carbohydrate chains, or glycans, or in drug delivery systems such as vesicles bearing polyethylene glycol chains and carrying therapeutic molecules. The self-organization of the chains on the spherical surface dictates the stability and functionality of the latter and is determined by key factors such as the interchain, chain–surface interactions, excluded volume, conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…Self-assembly of lipids into bilayers and vesicles is computationally efficient and reproducible in the Martini framework (Sharma et al, 2015). The selforganization of polyelectrolytic dendron-grafted amphiphiles (Figure 3A) within a lipid vesicle bilayer and its implications on the stability of the vesicle under different pH has been demonstrated using the Martini model (Banerjee et al, 2021;Banerjee and Dutt, 2023b). Peptide aggregation (Figures 3B, C) is accurately captured as a function of the concentration (Guo et al, 2012;Mushnoori et al, 2018; Frontiers in Soft Matter frontiersin.org Mushnoori et al, 2023).…”
Section: Coarse-grained Models With Intermediate Resolutionmentioning
confidence: 95%
“…Self-assembly of lipids into bilayers and vesicles is computationally efficient and reproducible in the Martini framework (Sharma et al, 2015). The selforganization of polyelectrolytic dendron-grafted amphiphiles (Figure 3A) within a lipid vesicle bilayer and its implications on the stability of the vesicle under different pH has been demonstrated using the Martini model (Banerjee et al, 2021;Banerjee and Dutt, 2023b). Peptide aggregation (Figures 3B, C) is accurately captured as a function of the concentration (Guo et al, 2012;Mushnoori et al, 2018; Frontiers in Soft Matter frontiersin.org Mushnoori et al, 2023).…”
Section: Coarse-grained Models With Intermediate Resolutionmentioning
confidence: 95%
“…Hence, the process of self-assembly is inherently multiscale. The extended dynamics underlying the self-assembly process can be captured using reduced models, such as coarse-grained (CG) representations of the molecules. To that end, another study adopted the CG explicit solvent Martini model to resolve the mechanisms underlying the self-assembly of FFF. The study reported the spontaneous formation of solid core nanospheres and nanorods within which the peptides were predominantly antiparallel to each other.…”
Section: Introductionmentioning
confidence: 99%